الشباب الجزائري بين اللبطالة الاختيارية وقيم العمل - ربحة, عبدالعالي; خواجة, عبدالعزيز (جامعة الوادي - University of Eloued, 2023)
يحاول هذا المقال ملامسة إشكالية ثقافة العيب في العمل عند الشباب الجزائري، هذه الثقافة التي تمنع الشباب من ممارسة العمل المهني وتفضيلهم البطالة عنها، حيث ترتكز هذه الدراسة على تحليل المعطيات الإحصائية ومناقشتها بالإضافة إلى الاستعانة بالشواهد الميدانية والمؤشرات الملموسة التي تجسد ملامح قيمة العمل وتجلياته في النشاط الفلاحي ومهنة البناء. توصلت هذه الدراسة إلى مجموعة من النتائج كان أبرزها: - وجود نزيف حاد في اليد العاملة بقطاع الفلاحة والبناء بالإضافة إلى شيخوخة عمالتها. - إنتاج الشباب لمفاهيم سوسيولوجية تدل على فكرة "الربح السريع" بأقل جهد ممكن. - تفضيل الشباب للأعمال الحرة خارج الفلاحة والبناء، مبررين ذلك بدعوى التخلص من المسؤولية والقيود القانونية. Abstract: This article attempts to address the problematic of shame culture in work among Algerian youth. This culture prevents young people from engaging in professional work and preferring to be unemployed. This study is based on the analysis and discussion of statistical data, as well as on the use of field evidence and concrete indicators that reflect the value of work and its manifestations in agricultural activity and the construction profession. This study produced a series of findings, most notably: - Severe labor shortage in the farming and construction sectors, and aging labor force. - Young people’s creation of sociological concepts that denote the idea of “quick profit” in the least effort possible. - Young people’s preference for entrepreneurship outside of farming and construction to get rid of responsibility and legal constraints.
مقال
Keywords: التكوين المهني؛ القوى العاملة؛ القطاع غير الرسمي؛ البطالة الاختيارية؛ ثقافة العيب; shame culture, vocational training, labor force, informal sector, voluntary unemploymen